Liver resection for the treatment of complex bile duct injury (Revista Argentina de Cirugía, 2026)
Bile duct injury represents a serious health problem, with its incidence doubling since the advent of laparoscopic cholecystectomy. In cases of complex lesions affecting the hepatic confluence, association with vascular injuries, hepatic atrophy, cholangitis or failed repair, treatment is often challenging. We report the case of a female patient with a complex bile duct injury due to vascular involvement of the right hepatic pedicle who developed right liver atrophy. In the presence of septic complications,hepatectomy was necessary, along with a definitive repair of the biliary tract, resulting in positive outcomes.
Keywords: hepatectomy; bile duct injury; sepsis